Green infrastructure in cities and towns in Southeast Asian countries: quest for research - Said, Ismail; Mansor, Mazlina (2011)
The cities in Southeast Asia are rapidly urbanised. Urbanisation in the region causes urban residents to live in a city with less balanced ecological system. Green infrastructure is known to be a vital indicator for urban environmental sustainability. The green infrastructure is all landscape types comprise of greenery and open spaces. Its network of park, playing field, pocket and incidental green space and neighbourhood space that is linked by tree-lined streets and waterways around and between urban areas provides green lung for cities, hence promotes healthy society through spaces for recreational, social and leisure activities. These are the places where urban residents have access and contact with nature, and interactions with other individuals. This paper explores the roles of green infrastructure in the Southeast Asian cities and towns, and its implications to urban residents‟ well-being. The green infrastructure acts as an important countermeasure to alleviate negative effects of urbanisation to residents and urban ecological system. A multidisciplinary literature review on urban open space, greenery and urban natural ecosystem was conducted to assess the body of research that highlights green infrastructure in Southeast Asia cities which include Jakarta, Singapore, Kuala Lumpur, Manila and Bangkok. The major themes derived from the findings were categorised into three: (i) quantity of existing green infrastructure, (ii) studies on green infrastructure contributions to well-being of urban residents, and (iii) significant attribute parameters that emerged from the studies. The review has found that even though the concept of green infrastructure may be new for many countries in the region, the areas of research have gained recognition in the urban public health dimension. In other words, the governments of the region must consider urban residents‟ health derived from green infrastructure to be of important resources for future urban sustainability. There are also challenges especially on green infrastructure‟s implementation that need to be addressed in city planning and urban design. The findings implicates that accumulation of research can promote public health of Southeast Asian cities that ultimately lead to environmental sustainability.